2005
DOI: 10.1002/ange.200502606
|View full text |Cite
|
Sign up to set email alerts
|

Mechanismus‐basierte Entwicklung eines sequenzselektiven ROMP‐Katalysators für die Copolymerisation von Alkenen

Abstract: Wir berichten hier von der Entwicklung eines Katalysators für die ringöffnende Metathesepolymerisation (ROMP), [1] der in einer Mischung von Cycloocten und Norbornen die Monomere vorzugsweise abwechselnd in die Polymerkette einbaut. Zwar gibt es bereits einige Berichte über gleichmä-ßige Copolymerisationen, aber außer in der Radikalcopolymerisation sind hoch selektive Systeme nur selten gefunden worden. Die Palladium-katalysierte Copolymerisation von Ethen und Kohlenmonoxid [2] und die Ringöffnungspolyme-risat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 14 publications
0
18
0
3
Order By: Relevance
“…By using a NBE/COE ratio of 1:50, the corresponding copolymers contained 95-97 % alternating diads (Table 1). A representative 13 C NMR spectrum of such a copolymer prepared by the action of 5 is shown in Figure 1. The signals for the alternating copolymer are observed around d = 135.0 and 128.5 ppm.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…By using a NBE/COE ratio of 1:50, the corresponding copolymers contained 95-97 % alternating diads (Table 1). A representative 13 C NMR spectrum of such a copolymer prepared by the action of 5 is shown in Figure 1. The signals for the alternating copolymer are observed around d = 135.0 and 128.5 ppm.…”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8][9][10][11][12] In 2005, Chen et al reported on the mechanism-based design of a ROMP initiator for sequence-selective copolymerization. [13,14] Generally, both selectivity and reactivity of Grubbs-or GrubbsHoveyda-type initiators is governed by the nature of the Nheterocyclic carbene (NHC), [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] the alkylidene, [31][32][33][34][35][36][37][38][39][40][41][42] or the (pseudo)halide ligands. [43][44][45][46][47][48][49][50][51][52][53] We recently reported on an alternative system for the synthesis of alternating copolymers based on Grubbs-type initiators containing ...…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these intermediates the alkylidene has moved from underneath the N-alkyl group to underneath the N-aryl group in accordance with recent work by Chen and co-workers. [19] It is difficult to say with any certainty whether intermediate B or C ("side-binding" or "bottom-binding" model) is actually responsible for the observed ees in the desymmetrization reactions. However, it is clear that the N-alkyl group of the NHC ligand has a direct effect on the ees of the desymmetrization.…”
Section: Resultsmentioning
confidence: 99%
“…[22] Die entscheidende Entdeckung war, dass in Gegenwart von nur 1 Mol-% rac-40 die RCM von 33 binnen 1 h mit mehr als 98 % Umsatz abläuft und das gewünschte Produkt rac-35 in 79 % Ausbeute liefert (Schema 11 Der Entwurf eines chiralen Ru-Komplexes, der in racemischer Form für sequenzselektive Copolymerisationen genutzt wurde, [30] demonstriert eindrucksvoll, wie chirale Katalysatoren ungewöhnliche Selektivitätsprofile liefern kön-nen. [31] Wie Schema 12 zeigt, hat der stereogene Ru-Komplex eine vergleichsweise stabilere diastereomere Form (41 und 42), in der sich das Carben neben dem sterisch weniger anspruchsvollen Phenylsubstituenten des Phosphanliganden befindet (Schema 12).…”
Section: Mehr Als Enantioselektivität: Zur Bedeutung Chiraler Katalysunclassified